An anthology of the arts and crafts movement writings by Ashbee, Lethaby, Gimson and their contemporaries - Ashbee, C. R. (Charles Robert) 1863-1942; Lethaby; Gimson (Lund Humphries, 2005)
This anthology includes contributions from key practitioners of the Arts and Crafts Movement as well as from commentators in newspapers and journals. It provides both an introduction to the ideas behind the Arts and Crafts Movement in England in its own words and a vivid picture of the people and events, which shaped the Movement.